Exosomes Derived from Umbilical Cord Mesenchymal Stem Cells Alleviate Mifepristone-Induced Human Endometrial Stromal Cell Injury. (25th January 2020) - Wang, Jianye; Hu, Ruomeng; Xing, Qiong; Feng, Xinghao; Jiang, Xiaohua; Xu, Yuping; Wei, Zhaolian
Abstract : The human endometrial stromal cells (hEndoSCs) could maintain endometrial homeostasis and play a critical role in repairing endometrial injury. Mesenchymal stem cells (MSCs) significantly increase the proliferation of damaged hEndoSCs and protect them from apoptosis. Recent studies indicated that exosomes derived from stem cells could be recruited to damaged tissues for regeneration, which exhibit the potential for stem cell therapy as therapeutic vectors. In this study, we isolated human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-Exos) and investigated the effects of hUCMSC-Exos on mifepristone-induced hEndoSC injury. Exosome uptake and cell proliferation as well as cell apoptosis of damaged hEndoSCs treated with hUCMSC-Exos were detected. We also assessed the expression of apoptosis-related proteins and the PTEN/AKT signaling pathway. We found hUCMSC-Exos improved the proliferation of damaged hEndoSCs and protected hEndoSCs from the mifepristone-induced apoptosis. hUCMSC-Exos upregulated Bcl-2 level as well as downregulated Cleaved Caspase-3 level and activated the PTEN/AKT signaling pathway to regulate the proliferation and antiapoptosis. These results indicated hUCMSC-Exos protected hEndoSCs from mifepristone-induced apoptosis and played an active role in repairing the damaged hEndoSCs through the PTEN/AKT signaling pathway in vitro . hUCMSC-Exos may hold great promise in the cell-free therapy of endometrial injury.